XPS study on passivation behavior of naturally formed oxide on AlFeCuCrMg1.5 high-entropy alloy - Kumar Dewangan, Sheetal; Kumar, Saurav; Maulik, Ornov; Pillai, Gokul M.; Kumar, Vinod; Ahn, Byungmin (Chemical Physics Letters, 2024)
High-entropy alloys have exceptional oxidation resistance due to their passive oxide film. In this study, photoelectron spectroscopy was used in a modern atomic-scale in situ initial oxidation analysis process to determine the oxidation behavior and elemental variation on its breakdown. Furthermore, the behavior of natural oxide formed on the AlFeCuCrMg1.5 HEA after the exposure of the alloy to the atmosphere for one hour, one day, and seven days was investigated in detail. Through a survey scan, the elements present on the oxidized surface were determined and quantified. Additionally, the seven-day-exposed HEA was depth-profiled and discovered drastic modifications in the alloy.
Keywords: Analysis process; Atomic scale; High entropy alloys; Initial oxidation; Natural oxides; Oxidation behaviours; Oxidized surfaces; Passive oxide films; Spark-plasma-sintering; High entropy alloy; Mechanical alloying; Oxidation; Spark plasma sintering; XPS